The Use of Calcium Phosphate-Based Starter Pellets for the Preparation of Sprinkle IR MUPS Formulation of Rosuvastatin Calcium - Krzysztof Cal; Barbara Mikolaszek; Tobias Hess; Markos Papaioannou; Joanna Lenik; Patrycja Ciosek-Skibińska; Helene Wall; Jadwiga Paszkowska; Svitlana Romanova; Grzegorz Garbacz; Daniel Zakowiecki (MDPI AG, 2023)
Sprinkle formulations represent an interesting concept of medicinal products aimed at the steadily growing population of patients suffering from swallowing difficulties (dysphagia). In the present work, immediate-release sprinkle MUPS (multiple-unit pellet system) containing rosuvastatin calcium as a model drug substance was successfully developed. The formulation was prepared by drug layering technique using novel calcium phosphate-based starting pellets (PharSQ® Spheres CM) of three different particle sizes. The study showed that the developed multiparticulates were characterized by uniform distribution of coating layers thickness, as well as fast dissolution rate (more than 85% of rosuvastatin calcium dissolved within 30 min, as required by the relevant USP/NF monograph). Rosuvastatin calcium, like other statins, has a bitter, unpleasant taste. Investigations conducted with an electronic tongue suggested that the developed formulation achieved the desired taste-masking efficiency. The effect was found to be particle size-dependent, improving as the size of the multiparticulates increased.